A novel 3D cavity diplexer with compact size using LTCC technologies for V‐band wireless communication systems. Issue 2 (18th June 2014) - Chu, Hui; Bian, Lei; Guo, Yong Xin
ABSTRACT In this article, a novel concept of 3D integrated V‐band diplexer, which permits the realization of compact size using a dual‐mode cavity and four single‐mode cavities, has been realized in low‐temperature cofired ceramic technologies. The dual‐mode cavity resonator acting as one resonator for both Rx and Tx filters is developed to generate two resonant modes (TE102 and TE103) at the center frequency of Rx (56.5–58.5 GHz) and Tx (64–66 GHz) channels, separately. Meanwhile, this dual‐mode cavity becomes the interconnect between Rx/Tx channels and help to realize good isolation without using conventional T‐junction. In the measurement, each filter designed for Rx and Tx channels exhibits excellent performance. Channel‐to‐channel isolations better than 35 dB across the Rx band and better than 32.5 dB across the Tx band are also obtained. © 2014 Wiley Periodicals, Inc. Int J RF and Microwave CAE 25:141–145, 2015.